THE EFFECT OF MICRO-NUTRIENT MIXED SUPLEMENTATION THROUGH DRINKING WATER AGAINST PHYSICAL QUALITY OF CHICKEN EGGS - G. K.I, Purnamayana; Astawa, I P. A.; Suasta, I M. (Jurnal Peternakan Tropika; Vol 8 No 1 (2020): Issue 8 No. 1 (2020); January - April, 2020)
This study aims to determine the effect of micro-nutrient mixture supplementation through drinking water on the physical quality of chicken eggs for 4 months in Candikusuma Village, Melaya District, Jembrana, Bali. The design that will be used is a Completely Randomized Design (CRD) with three treatments and five replications. The treatments are chickens given drinking water without supplementation of micro-nutrient mixtures as a control (P0), chickens given drinking water plus 5 grams of micro-nutrient mixture supplementation in 10 liters of water (P1), chickens given drinking water plus 10 grams supplementation of a mixture of micro-nutrients in 10 liters of water (P2). The variables observed were egg weight, egg yolk percentage, egg white percentage, egg shell percentage, egg shell thickness and egg specific gravity. The results of this study showed that the P1 and P2 treatments significantly (P <0.05) increased egg weight, egg white percentage, egg shell percentage, egg shell thickness and egg specific gravity compared to P0 treatment. However, in the percentage of egg yolk there was a decrease (P <0.05) compared to the P0 treatment. Based on the results of this study it can be concluded that supplementation of 5 gr and 10 gr micro-nutrient mix levels in 10 liters of water through drinking water can increase egg weight, egg white percentage, egg shell percentage, egg shell thickness and egg specific gravity and reduce the percentage of yolk chicken eggs. Keywords: Eggs, micro-nutrient supplementation, physical quality .